2022
DOI: 10.1039/d2fo01221a
|View full text |Cite
|
Sign up to set email alerts
|

Codonopsis pilosulapolysaccharides attenuateEscherichia coli-induced acute lung injury in mice

Abstract: Acute lung injury (ALI) is an inflammatory lung disease could be caused by bacterial infection. Lipopolysaccharide (LPS), a prototype pathogen-associated molecular pattern (PAMP) from gram-negative bacteria such as Escherichia coli...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…For instance, Morchella esculenta polysaccharides can boost oxidative enzyme reactions and lower cell death, hence reducing oxidative stress [35]. Similar to this, Codonopsis pilosula polysaccharides [36] and Lentinus edodes polysaccharides [37] can prevent lung damage by inhibiting the production of pro-inflammatory cytokines, including TNF-α and IL-6. As a result, we speculated that ALP might be a useful medication for preventing ALI.…”
Section: Discussionmentioning
confidence: 85%
“…For instance, Morchella esculenta polysaccharides can boost oxidative enzyme reactions and lower cell death, hence reducing oxidative stress [35]. Similar to this, Codonopsis pilosula polysaccharides [36] and Lentinus edodes polysaccharides [37] can prevent lung damage by inhibiting the production of pro-inflammatory cytokines, including TNF-α and IL-6. As a result, we speculated that ALP might be a useful medication for preventing ALI.…”
Section: Discussionmentioning
confidence: 85%
“…How to prevent and deal with cow bacterial mastitis is an important problem in public health. LPS are a major component of Gram-negative bacteria, causing similar inflammatory responses to those caused by intact E.coli [ 19 ]. Some studies have shown that IL-17A is an important effector of mammary immune responses to E.coli , and local enhanced production of IL-17A can improve the outcomes of early infections [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of the inflammatory response is the up-regulated secretion of cytokines and chemokines. For example, the excessive production of various cytokines and chemokines plays a vital role in the pathophysiology of septic shock caused by bacterial infections [ 19 , 21 ]. Studies by Ma et al show that with the incidence of mastitis, the secretion levels of cytokines IL-1β, IL-6, and TNF-α will significantly increase, and IL-1β, IL-6, and TNF-α are important inflammatory cytokines that can trigger immune responses in organisms [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…53,54 To the best of our knowledge, this is the first study on the effect of ACs in LIGAO on the antitussive ability and the protection of lung tissue from inflammatory injuries. Furthermore, the changes in TNF-α and IL-1β are related to the MAPK and NF-κB signaling pathway 55 and the regulatory effect of Fru-Asp on the MAPK and NF-κB signaling pathway activation are not been investigated. Thus, more studies are required to be conducted.…”
Section: Discussionmentioning
confidence: 99%